Perceived risks, barriers and stages of change on smoking cessation among the Malay security guards in a public university in Kuala Lumpur - Moy, Foong Ming; Ab Sallam, Atiya; Wong, M.L. (2008)
Introduction: The objective was to evaluate the perceived risks, barriers and stages of change on smoking cessation among the Malay male security guards. Materials and Methods: In the year 2004, a cross sectional survey was conducted on a group of security guards working in the campus and the hospital of a public university in Kuala Lumpur. Universal sampling (n=210) was conducted with a response rate of 88.6. A selfadministered questionnaire was used to survey the participants on their smoking status, stages of change, perceived risks and barriers to smoking cessation. Results: There were 37 current smokers and 23.7 exsmokers. The mean year of smoking was 19.2 + 8.1 and the number of cigarettes smoked was 16.4 + 8.0 per day among the current smokers. About two-third of the smokers perceived the amount smoked currently was bad for health. However, only 23.3 and 30.9 of the smokers perceived themselves to be at higher risk for lung cancer and heart disease respectively. The three main reasons to quit smoking were health reasons, doctorsâ advice and cost. The main barriers were addiction (53.3) and stress (28.3). Most of the smokers (42) were in the pre-contemplation stage with half of them not having thoughts of quitting. Conclusion:The smokers had misperception on smoking and majority was at the pre-contemplation stage of change in smoking cessation. The findings of this survey add on to the existing literature about the perception of risks, barriers and stages of change to smoking cessation. This will provide valuable information on the planning and delivering of smoking cessation programmes in the local context.